Autonomic Function test in person with Obesity aAmong Mid-Western Population of Nepal - Neupane Pant, Bhawana; Goit, Rajesh Kumar; Panta, Manoj; Neupane, Ashish; Bhargava, Pushpa (Journal of Nepalgunj Medical College, 2017)
Objective: Autonomic dysfunction qualifies a major public health problems owing to their high prevalence and incidence globally. Among many predisposing factor of autonomic neuropathy such as age, gender, genetic, diabetes etc, obesity also has significant . impact Although a lot of progress has been achieved in past decade on accessibility and awareness about health, the obesity remains impending and burgeoning health concern in Nepal. With this trend, we can foresee that the Body Mass Index (BMI) one of the commonly used indirect measure of obesity, might potentially turn out to be one of the leading factor of autonomic dysfunction. Methods: 100 healthy subjects were screened and divided into 2 groups- Group I (BMI>30) and Group II (BMI< 30). Height & weight were measured & BMI was calculated. Resting heart rate (RHR) was recorded with Lead II of ECG. Blood pressure (BP) and Heart Rate (HR) were recorded in supine position and on immediate standing. Cold pressure test (CPT): Resting BP was recorded in sitting position. Then the subjects were asked to immerse the hand in cold water, and the BP was measured from other hand. Data was analyzed using SPSS 16 (Statistical Package for Social Science). Result: Our result showed that RHR of Group I (79.32±4.22) was higher than that of Group II (74.38±7.26). However, on student –T test, BP and HR response to immediate standing (P=0.34 &P=0.23 respectively) were non-significant between group I and group II person. When the correlation was done for the change in BP in response to CPT in between obese and non-obese person it was found to be significant (P=0.04). Conclusion: Our data suggests that the BMI can be a predictor of autonomic dysfunction.